Beyond economic rationality: Gendered labor, moral economy, and women's working duration in an Islamic educational institution - Rahma Sandhi Prahara; Farida Ulvi Na’imah; Diah Syifaul A’yuni; Sundari Sundari; Aulia Herdiani; Salshabila Syifa Nurendra (An-Nisa’ Journal of Gender Studies, 2026)
The increasing participation of women in the labour market has not been accompanied by an adequate understanding of the factors shaping their working hours. In Islamic educational institutions, women’s working hours are determined by the interaction of economic incentives, gender relations, institutional demands, and moral-religious values. This study examines the determinants of working hours and their relationship with the household well-being of female educators through the perspectives of Household Economics, Gender Studies, and Moral Economy. An explanatory sequential mixed-methods design was employed, integrating multiple linear regression, mediation analysis, and thematic analysis of survey data collected from 100 female educators and purposively selected in-depth interview participants. The quantitative findings indicate that working hours are significantly influenced by economic, institutional, and sociocultural factors, with administrative workload emerging as the strongest determinant. Flexible work arrangements and domestic support increase women’s working hours, whereas gender norms constrain them. Working hours also mediate the relationships between several determinants and household well-being. The qualitative findings reveal that women’s labour allocation extends beyond economic rationality, as it is continuously negotiated through institutional expectations, domestic responsibilities, gender relations, moral values, and religious commitments. This study contributes to Gender Studies by demonstrating that women’s labour allocation is a gendered and socially embedded process. It also extends the Household Economics perspective by integrating Moral Economy and proposes the concept of faith-embedded labour supply to explain women’s labor-supply behavior within faith-based educational institutions.